A Model for the Reduction of Flood Peak Discharge (ΔQp) Due to the Retarding Basin - Yuwono, Hari; Limantara, Lily M.; Sholichin, Moh.; Siswoyo, Hari (Civil Engineering Journal, 2025)
This research aims to develop a model for flood peak discharge reduction (ΔQp) through the placement of retarding basins within a watershed system, represented by the area ratio of the controlled watershed (RAk) and the maximum storage capacity of the retarding basin (Vk). The area ratio of the controlled watershed (RAk) is defined as the ratio between the catchment area of the retarding basin and the total watershed area (Ak/A). The methodology involves simulating various retarding basin placements (RAk) and different maximum storage capacities (Vk) for several flood return periods (QT). This study was conducted in the urban agglomeration area of Wonosari, Gunungkidul Regency, Special Region of Yogyakarta, Indonesia. The placement and utilization of retarding basins result in varying levels of flood peak discharge reduction (ΔQp) at the downstream control point (Taman Pancuran), depending on the maximum storage capacity of the retarding basin (Vk) and its placement within the watershed (RAk). The resulting empirical equations for flood peak discharge reduction (ΔQp) using the retarding basin method are as follows: ΔQp = 0.105654 − 0.014593 Vk − 0.029251 RAk + 0.011089 QT for Vk values in the range (V1–V4) = 36.4–208.8 × 10³ m³, and ΔQp = 1.374989 − 0.003702 Vk − 0.338381 RAk + 0.004773 QT for Vk values in the range (V4–V200) = 136.2–7039.1 × 10³ m³. An observed anomaly was identified, where ΔQp became positive at small values of Vk and RAk, indicating an increase in peak discharge (Qp).